DATA MINING TO PREDICTE THE TIME OF KHATAMAN TAHFID STUDENTS TAHFID PPTQ AL-ASY'ARIYYAH USING C4.5 ALGORITHM - Muhamad Maulana Ikhsanul Khafidli; Muhamad Fuat Asnawi; Adi Suwondo; Sukowiyono; Dimas Prasetyo Utomo (Clean Energy and Smart Technology, 2023)
PPTQ Al-Asy'ariyyah is an Al-Qur'an-based Islamic boarding school where most students memorize the Al-Qur'an. This study uses data mining to calculate how many students are late in completing their memorization and the factors that influence it by using the C4.5 algorithm. Algorithm C4.5 has a decision that can give the desired result. The results of this study found several factors that influence the punctuality of khatam and several factors. Of the 250 students located, 96 could complete their memorization on time, and 154 were off target or on time. Based on what was obtained from the study results, the timeliness of completing the completion is sufficient.